A customer-centric IoT-based novel closed-loop supply chain model for WEEE management. (January 2023) - Guo, Rui; Zhong, Zhaowei
Abstract: Waste electrical and electronic equipment (WEEE) has been one of the widest and soaring solid wastes worldwide. Circular economy, as a sustainable paradigm, promotes closing the loop of e-products to prolong the life of WEEE. Hence, a sustainable Internet of things (IoT)-based closed-loop supply chain (CLSC) system is established considering the economic, environment and social dimensions. Due to the reality constraints, a simulation model with two scenarios is constructed to consider the customers' behavior in the system. The attribute importance of customers' behavior is analysed. Second-hand price and buy back price are shown to be two highly important factors, followed by peer pressure and social influence. Additionally, we present a sustainability assessment with the extant system using life cycle assessment, showing that our proposed system is more sustainable. Appropriate WEEE management using the proposed IoT-enabled system makes more profit and can reduce more greenhouse gas emissions and heavy metal contamination. In addition, with applying the proposed system, the number of people being protected from diseases caused by heavy metals can be significantly reduced.